Kendall's Advanced theory of statistics. - Stuart, Alan; Ord, J. K.; Kendall, Maurice G. (London : E. Arnold, 1994)
The new version consists of three core volumes: the present volume on Distribution Theory, and the two volumes on Inference: Classical and Bayesian.
Includes bibliographical references and indexes.
osc 1/11/2021
Loans
Keywords: Mathematical statistics